The promises of digital bank accounts for low-income individuals - Karla Hernández Romero; Diego Alejandro Vera Cossío; Bridget Hoffmann; Camilo Pecha (Inter-American Development Bank (IDB), 2024)
The push for adopting digital modes of payment rests on three promises: increased efficiency of transactions, increased financial inclusion, and improvements in the financial well-being of low-income individuals. We experimentally test the extent to which these promises are fulfilled. We exploit the random assignment into an intervention to encourage direct deposits of recurrent government benefits into digital bank accounts in Colombia. Switching from cash to direct deposits reduces disbursement errors and increases access to benefits among eligible beneficiaries. It also increases the ownership of bank accounts, the demand for formal loans, and loan take-up among individuals without a financial history. However, we do not find evidence of improvements in financial well-being across any of our metrics.
Keywords: D90; H53; I38; 330; Technology adoption; Social protection; Formal financial products